"Notes and Queries … " – That Wren drawing. Issue 1 (3rd April 2021) - Fergusson Baugh, Cat
ABSTRACT: In this article I will expand on work presented in 'Haptic Insights: Model Making as Historical Methodology' (Fergusson Baugh 2018 ) and demonstrate the value of the methodologies proposed there on a case study reconstruction of the second Drury Lane theatre (1674) initially prepared for the THEATRON project. I will explore the history of this building through a procedural engagement with source material and the development of a virtual model. I will also explore how an apparently inconsequential inconsistency in the section can account for Langhans, Mulling and Koenig's disagreement (and resolve which of them was right), and how a process of computer modelling suggests a haptic insight into a more human history of a drawing that has been forcefully torn up but retained and carefully conserved for 350 years.